Efeitos da experimentação no cotidiano letivo no ensino médio - Paula, Carlos Eduardo Rodrigues de [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
In this work, it was studied the effects of the experimentation in the physics teaching. Beginning from the theoretic reference and discussions, the objective was prove the efficiency of researches of this nature related to two main aspects of a class: The aroused interest in the students and the facilitating action on the understanding of the theory. For such objective, using the comparison, it was chosen two distinct classes, but the more similar possible, so that, in one of them, it was showed a tradition class, lectures and in another, a class using experimentation to contemplate the theory. To manage a way to rate these aspects, it was made a conceptual questionnaire, requiring only concepts rather than mathematics and equations, besides specific interviews to rate the opinion of the student related to each method. The observations in classes and of the reactions of the students also were of a big value to analysis. After the experimental class completed, it may analyze and conclude some positive points related to experimental methods: As for the opinion of the students, the approval was big, and the majority opined to this class as being “more interesting”. On the point of view of learning, it had a sensitive improvement of grades, but with more mature answers, deep and autonomous, if looking at a general vision

Neste trabalho estudou-se os efeitos da experimentação no ensino de física. Partindo de referencial teórico e discussões, o objetivo era comprovar a eficiência de recursos dessa natureza em relação à dois aspectos principais de uma aula: o interesse despertado no alunos e a ação facilitadora no entendimento da teoria. Para tal, usando de comparação, escolheram-se duas salas distintas, porém o mais semelhante possível, para que, em uma delas, fosse apresentada uma aula tradicional, expositiva e em outra, uma aula com uso de experimento para contemplar a teoria. Para conseguir um meio de avaliar esses aspectos, foi bolado um questionário conceitual, exigindo realmente conceito ao invés de matemática e formulas, além de entrevistas especificas para avaliar a opinião dos alunos em relação a cada método. As observações de aula e das reações dos estudantes também foram de grande valia para análise. Após completas as aulas amostra, pode-se analisar e concluir alguns pontos positivos em relação ao método experimental: Quanto à opinião dos alunos, a aprovação foi grande, sendo que grande maioria opinou para essa aula como sendo ‘mais interessante’. Do ponto de vista de aprendizado, obteve-se sensível melhora de notas, mas com respostas mais maduras, profundas e autônomas, se olhando com uma visão geral
Keywords: Física - Estudo e ensino; Ensino - Meios auxiliares; Ensino médio; Pratica de ensino; Aprendizagem; Fisica experimental; Physics - Study and teaching; Teaching - Aids and devices; Learning; Physics--Experiments